Implementation of Sets-Based Iot Integrated Gamification on Physics Materials to Improve Student Learning Outcomes - Farah Lailatul Nur Alifiyah; Thoriqi Firdaus (J-SES : Journal of Science, Education and Studies, 2023)
This study aims to improve student learning outcomes using the concept of SETS-based IoT integrated gamification in physics materials. The method in this study is Pre-experimental one group pretest-posttest which is used to measure student learning outcomes before treatment and after treatment. The subjects of this study were class VIII students of Junior High School AR RISALAH Sumenep Regency. The results showed that the implementation of SETS-based IoT integrated gamification in learning can improve student learning outcomes. This can be seen from the average posttest value which is higher than the average pretest value, which is a difference of 26.67. Based on the analysis of paired t-test data using SPSS 20, it shows that the significance value obtained is the sig pretest value. 0.130 while the posttest value is sig. 0.200. P-value (sig. (2-tailed)) obtained a value of 0.000 which means less than 0.05. So that way it can be concluded that H0 is rejected, while H1 is accepted, namely there are differences in learning outcomes before and after treatment by implementing SETS-based IoT integrated gamification on physics materials.Â